2021
DOI: 10.1038/s41438-021-00533-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of early-stage incompatible and compatible interactions between grapevine and P. viticola

Abstract: Wild grapevines can show strong resistance to the downy mildew pathogen P. viticola, but the associated mechanisms are poorly described, especially at early stages of infection. Here, we performed comparative proteomic analyses of grapevine leaves from the resistant genotype V. davidii “LiuBa-8” (LB) and susceptible V. vinifera “Pinot Noir” (PN) 12 h after inoculation with P. viticola. By employing the iTRAQ technique, a total of 444 and 349 differentially expressed proteins (DEPs) were identified in LB and PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…The main documented responses so far are the local deposition of CW materials, known as papillae or the cross-linking among components of the matrix, in order to hinder the access of the pathogens to the protoplast [ 22 , 31 , 32 ]. Recently, several transcriptomic and proteomic analysis would indicate that CW remodeling is a widely extended process in nature [ 33 , 34 , 35 , 36 ], however the detailed characterization of the changes that take place in muro after bacteria attack remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The main documented responses so far are the local deposition of CW materials, known as papillae or the cross-linking among components of the matrix, in order to hinder the access of the pathogens to the protoplast [ 22 , 31 , 32 ]. Recently, several transcriptomic and proteomic analysis would indicate that CW remodeling is a widely extended process in nature [ 33 , 34 , 35 , 36 ], however the detailed characterization of the changes that take place in muro after bacteria attack remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…By using DLR and EMSA assays, infection site (Torres and Dangl, 2005;Lehmann et al, 2015;Camejo et al, 2016;Segal and Wilson, 2018). And as a signal molecule, it participates in the strengthening of cell wall and promotes pathogenesis-related genes (PRs) (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase enzymes encoded by the Rboh gene could cause the accumulation of ROS, which is critical in the defense system of plants, because it can inhibit the pathogens infection process by directly inhibiting pathogen or inducing hypersensitivity at the infection site ( Torres and Dangl, 2005 ; Lehmann et al, 2015 ; Camejo et al, 2016 ; Segal and Wilson, 2018 ). And as a signal molecule, it participates in the strengthening of cell wall and promotes pathogenesis-related genes ( PRs ) ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Torres et al (2002) research confirmed the absence of the NADPH oxidase genes, AtRbohD and AtRbohF, suppress ROS production and the defense response of Arabidopsis against pathogen attack. ROS levels depend on the balance between ROS production and scavenging, and excess ROS could injure cells ( Mittler et al, 2004 ; Liu et al, 2021 ). ROS amounts depend both on enzymatic and non-enzymatic scavenging molecules such as PrxII, APX, dehydroascorbate reductase (DHAR), and 1-Cys peroxiredoxin (1-CysPrx), which offer a highly efficient system for maintaining ROS homeostasis ( Supplementary Table 6 ).…”
Section: Discussionmentioning
confidence: 99%